2018
DOI: 10.1111/jace.16080
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the properties of niobium pentoxide for use in dye‐sensitized solar cells

Abstract: This work demonstrates the obtention of Nb2O5 nanoparticles by the microwave‐assisted hydrothermal synthesis method in a fast way and with the use of low temperatures. The heat treatment applied on the samples promotes the phase change in Nb2O5 from pseudohexagonal to orthorhombic as the temperature increases, with a particle size between 7.3 and 32.6 nm. The band gap of the samples decreases with increasing temperature, obtaining a minimum value of 3.04 eV at 800°C. Dye‐sensitized solar cells (DSSC) were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 40 publications
(54 reference statements)
1
15
0
Order By: Relevance
“…The DSSC assembly was performed in different steps. First, for the photoanode, the conductive glass substrate FTO (fluorine-doped tin oxide, 7 X sq -1 , Sigma-Aldrich) was cleaned as previously described [11,24]. Nb 2 O 5 pastes were prepared using 300 mg of Nb 2 O 5 from each synthesis (CR, SG, PP, MAH), 18 lL of ethylene glycol, 15 lL of Triton-X, and an amount of ethanol between 75 and 150 lL.…”
Section: Dssc Assemblymentioning
confidence: 99%
See 3 more Smart Citations
“…The DSSC assembly was performed in different steps. First, for the photoanode, the conductive glass substrate FTO (fluorine-doped tin oxide, 7 X sq -1 , Sigma-Aldrich) was cleaned as previously described [11,24]. Nb 2 O 5 pastes were prepared using 300 mg of Nb 2 O 5 from each synthesis (CR, SG, PP, MAH), 18 lL of ethylene glycol, 15 lL of Triton-X, and an amount of ethanol between 75 and 150 lL.…”
Section: Dssc Assemblymentioning
confidence: 99%
“…Microwave-assisted hydrothermal synthesis is considered by many researchers to be an advantageous technique in relation to the other synthesis methods since it is easy to perform, completed in a relatively short synthesis time, and conducted at a lower temperature range, making it efficient for crystallization [43][44][45]. In a previous work, we demonstrated that Nb 2 O 5 obtained by this method presented good optical properties and photovoltaic responses [24].…”
Section: Graphical Abstract Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…The adoption of this synthesis method allows simplicity, speed and low cost in obtaining zinc titanates. The same method has already been used in other works involving the synthesis of titanium oxides [ 13 ] and other metals [ 14 , 15 ] as well as the manufacture of components for DSSC's [ 16 ] with excellent results related to electrical properties.…”
Section: Introductionmentioning
confidence: 99%